The combined effects of temperature and salinity on survival of larvae and juveniles of tropical abalone Haliotis asinina under laboratory conditions - Chaitanawisuti, Nilnaj; Nunim, Sirinun; Santhaweesuk, Wannanee (Journal of Research in Biology, 2012)
This paper reports on a 3 x 3 factorial design experiment conducted to examine the combined effects of temperature and salinity on survival of larvae and juveniles of tropical abalone Haliotis asinina under laboratory conditions for 96 h. The temperatures used were 25, 30 and 35°C and the salinities were 27, 30 and 33 ppt. Response surface contour diagrams were generated from the survival data to estimate optimal conditions. The highest survival of newly-hatched larvae, newly-settled juvenile and fully juveniles of H. asinina was obtained at the lowest temperature tested (25°C) with the highest salinity tested (33 ppt), while the lowest survival was obtained at the highest temperature tested (35°C) with the lowest salinity tested (27 ppt). Two - way ANOVA showed that survival of larvae, newly - settled juveniles and fully juveniles were significantly affected by temperature and salinity. A significant interaction between both factors occurred in newly - settled juveniles and fully juveniles but not for larvae. Multiple regression analysis indicated a higher correlation between salinity and survival of larvae H. asinina but a higher correlation between temperature and survival for newly - settled juveniles and fully juveniles. This study indicated that the optimal conditions for maximum survival of larval, newly - settled juvenile and fully juveniles were 27-30°C and 31-33 ppt, 26-29°C and 27-33 ppt, and 26-27°C and 31-33 ppt, respectively.